A relação entre religião e Estado sob a égide do direito fundamental da liberdade de religião - Sabaini, Wallace Tesch (2008)
This dissertation studies the religion freedom and the current relation between Church and State in Brazil, asking about the facticity of the laicity of State defended by Brazilian Constitution, as well as if it is real the fundamental right of religious freedom in Brazilian society. It is based on bibliographical, documental, electronic, and primary sources research. It also studies the court decisions on the subject. It describes the concept of Fundamental Law and its relation do the dignity of the human person, showing that that concept is affirmed in the course of human history as a consequence of social evolution. It also studies the dignity of the human person as a constitutional beacon directed to the fundamental rights defended by Brazilian Constitution. Its subject is the fundamental right of religious freedom and the different descriptions of that freedom in the juridical ordainment of Brazil. It presents the systems of relation between State and Religion and studies the relation between Brazilian State and the Church, showing the initial symbiosis between them and the slow process of rupture initiated with the Proclamation of Republic. Based on that, it elaborates an elenchus of derivates from religious freedom. In light of the extended list of fundamental rights perceives the unavoidability of the collision among them, which makes it necessary the definition of parameters presenting plausible juridical solutions. So, it presents the Theory of Principles since that theory the fundamental rights receive the nature of principles and, from that nature it can be deducted the maximum proportionality as criterion to conflict resolution. It examines a few cases of fundamental rights collision, abuse of protective rights and restriction of rights – all about religious freedom – in the light of the Theory of Principles. It observes, in the real situation, which one of the fundamental rights is better adapted to the situation, or which one offers a larger magnitude regarding the principle of human dignity. Finally, considers that, given the collision between fundamental rights, there are no previous parameters regarding the normative and the factual possibilities of each case, what makes it necessary deep reflection, and in order to not offer inadequate solutions, it becomes necessary to know the fundamental right of religious freedom in its whole manifestation. It also sees that the principle of separation between State and religion in the Brazilian Constitution needs to receive larger practical application, since there still are remaining cases of the older symbiosis between State and Roman Catholic Apostolic Church.